High SPOCK1 Expression Is Associated with Advanced Stage, T Value, and Gleason Grade in Prostate Cancer - Mei-Ling Chen; Cheng-Ju Ho; Chung-Min Yeh; Sung-Lang Chen; Wen-Wei Sung; Shao-Chuan Wang; Chih-Jung Chen (Medicina, 2019)
Background and objectives: Prostate cancer (PCa) is a common malignancy in males and has a relatively slower progression than other cancers. Our goal was to evaluate the clinical role of SPARC (secreted protein acidic and cysteine rich, osteonectin), cwcv, and kazal-like domains’ proteoglycan 1 (SPOCK1) in PCa. Materials and Methods: SPOCK1 expression was studied through the immunohistochemical staining of specimens from 71 patients with PCa. The correlation between SPOCK1 expression and clinicopathological features was quantitatively analyzed. We used Kaplan−Meier analysis and Cox proportional hazard models to analyze the prognostic value. Results: Of 71 PCa patients, high SPOCK1 expression was more likely to be seen in those with an advanced stage (p = 0.018) of the disease and an advanced tumor (T) value (p = 0.014). Patients in Gleason grade groups 3 and 4 had significantly higher SPOCK1 expression (p = 0.044 and 0.003, respectively) compared to those of Gleason grade group 1. However, this trend was not observed in patients in Gleason grade group 5. For the survival analysis, although it was not statistically significant, patients with a high SPOCK1 expression had a shorter median overall survival (6.2 years) compared to those with low expression (7.8 years). Conclusions: High SPOCK1 expression may be related to advanced clinicopathological features and possibly a poor prognosis. Further analysis with a larger patient base would help clarify this issue.